THE CHARACTERISTIC OF ACTIVITY LIMITATIONS CAUSED BY LUNG CANCER - Levkin V. G.; Achkasov E. E.; Zapariy N. S.; Paikov A.Y. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The article presents the characteristics of activity limitations caused by lung cancer taking into account clinical data, stages of the disease, and severity of the disability. The dynamics shows that the restrictions of the fist, second and third degrees relating to self-care, movement and labour activity make up the largest share in the structure of activity limitations while the restrictions of the fist, second and third degrees relating to communication constitute the smallest share.